(untitled) (Eurasian Medical Research Periodical, 2022)
PCOS is a heterogeneous complicated ailment with a well-defined etiology that affects the majority of women of reproductive age. The study’s purpose is to figure out what PON1 does, Mg, NO, and TAC activity in Iraqi women with PCOS. Eighty samples (40 PCOS patients and 40 controls) were collected between December 2021 and March 2022 for the study. Both groups had their Prolactin, luteinizing hormone (LH), follicle stimulating hormone (FSH), and body mass index (BMI) , fasting blood sugar (FBS), magnesium (Mg), and testosterone levels measured. ELISA was used to measure serum NO (nitric oxide), MDA (malondialdehyde), PON1 activity (paraoxonase 1), and TAC (total antioxidant capacity). When comparing the experimental group to the control group.In PCOS individuals, there was a significant increase in serum levels of LH, Testosterone, and Prolactin, as well as a decrease in serum FSH. Furthermore, FBS levels were considerably higher in PCOS patients, although serum magnesium levels were lower, indicating increased urine excretion of Mg in the presence of insulin. Changes in NO levels in PCOS are highly significant, serum PON1 activity was lower, while TCA was lower in the PCOS group.